2018
DOI: 10.1109/taes.2018.2798219
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Tracking Guidance for Aeroassisted Spacecraft Reconnaissance Mission Based on Receding Horizon Control

Abstract: This paper focuses on the application of model predictive control (MPC) for the spacecraft trajectory tracking problems. The motivation of the use of MPC, also known as receding horizon control, relies on its ability in dealing with control, state and path constraints that naturally arise in practical trajectory planning problems. Two different MPC schemes are constructed to solve the reconnaissance trajectory tracking problem. Since the MPC solves the online optimal control problems at each sampling instant, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…A reentry guidance and control system is usually divided into two subsystems, namely, an trajectory control system and an attitude control system [10]. Trajectory control is often fulfilled by carrying out two major steps: trajectory optimization [11] and trajectory tracking guidance [12]. Since a well-planned trajectory is a key for enhanced trajectory control of the HV, a large amount of research on developing trajectory optimization methods can be found [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…A reentry guidance and control system is usually divided into two subsystems, namely, an trajectory control system and an attitude control system [10]. Trajectory control is often fulfilled by carrying out two major steps: trajectory optimization [11] and trajectory tracking guidance [12]. Since a well-planned trajectory is a key for enhanced trajectory control of the HV, a large amount of research on developing trajectory optimization methods can be found [13], [14].…”
Section: Introductionmentioning
confidence: 99%
“…The attitude tracking control for rigid spacecraft has already attracted a great deal of interests during the last decades. Various nonlinear control methods for attitude tracking have been developed for rigid spacecraft with priori-known model parameters, such as nonlinear feedback control [1], [2], optimal control [3], [4], robust control [5], [6], or their integration [7]- [9]. During the on-orbit operation of spacecraft, the inertia matrix may be uncertain since the mass properties of spacecraft could be changed by the movement of onboard payloads, the rotation of solar arrays and the consumption of fuel [10].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in many published works that the trajectory design component plays a key role with regard to stable flight and improved control of the space vehicle [7,8]. A comprehensive overview of the motivation for the use of trajectory optimization in different space missions, together with various related trajectory optimization approaches, was made by Conway in 2011 [2].…”
Section: Introductionmentioning
confidence: 99%